Multifactorial modulation of susceptibility to l-lysine in an animal model of glutaric aciduria type I - Sauer, Sven; Opp, Silvana; Komatsuzaki, Shoko; Burgard, Peter; Okun, Jürgen G.; Kölker, Stefan (Biochimica et biophysica acta. Molecular basis of disease, 2015)
Glutaric aciduria type I is an inherited defect in l-lysine, l-hydroxylysine and l-tryptophan degradation caused by deficiency of glutaryl-CoA dehydrogenase (GCDH). The majority of untreated patients presents with accumulation of neurotoxic metabolites - glutaric acid (GA) and 3-hydroxyglutaric acid (3-OHGA) - and striatal injury. Gcdh−/− mice display elevated levels of GA and 3-OH-GA but do not spontaneously develop striatal lesions. l-lysine-enriched diets (appr. 235mg/d) were suggested to induce a neurological phenotype similar to affected patients. In our hands 93% of mice stressed according to the published protocol remained asymptomatic. To understand the underlying mechanism, we modified their genetic background (F1 C57BL6/Jx129/SvCrl) and increased the daily oral l-lysine supply (235-433mg). We identified three modulating factors, (1) gender, (2) genetic background, and (3) amount of l-lysine. Male mice displayed higher vulnerability and inbreeding for more than two generations as well as elevating l-lysine supply increased the diet-induced mortality rate (up to 89%). Onset of first symptoms leads to strongly reduced intake of food and, thus, l-lysine suggesting a threshold for toxic metabolite production to induce neurological disease. GA and 3-OH-GA tissue concentrations did not correlate with dietary l-lysine supply but differed between symptomatic and asymptomatic mice. Cerebral activities of glyceraldehyde 3-phosphate dehydrogenase, 2-oxoglutarate dehydrogenase complex, and aconitase were decreased. Symptomatic mice did not develop striatal lesions or intracerebral hemorrhages. We found severe spongiosis in the hippocampus of Gcdh−/− mice which was independent of dietary l-lysine supply. In conclusion, the l-lysine-induced pathology in Gcdh−/− mice depends on genetic and dietary parameters.